Designing Enterprise Architecture Using TOGAF Architecture Development Model (Case Study: BLC Course Institutions) - Sukiman Sukiman; Zulganef Zulganef (International Journal of Ethno-Sciences and Education Research, 2023)
Business development must be in line with the development of information and communication technologies to accomplish organizational goals effectively and efficiently. For the educational sector, stakeholders must create and construct information systems that are quick, exact, and accurate regarding business operations in achieving organizational objectives. Information system development must be created in accordance with the organization's strategy to fulfill the organization's information system requirements. BLC Course Institutions recognizes the need of developing an information system that can fulfill the requirements of the organization. The institutions planned to develop enterprise architecture to harmonize the current business strategy in BLC. As the course institute does not have a thorough enterprise architectural design, information system management and business practices are not aligned and lack maturity. So, it has an impact on the service that will be provided to customers. The Open Group Architecture Framework (TOGAF) Architecture Development Method was utilized to create this Enterprise Architecture. Data architecture, application architecture, technology architecture, and creating an implementation plan roadmap are included in enterprise architectural planning in BLC. The process of information architecture determining that was constructed refers to the procedures that had taken place in the educational system administration. The definition process covered in this study includes infrastructure, marketing, academic funding, learning planning, and learning execution. This research produced a blueprint that was utilized to enable integrated business processes. The enterprise architecture created during this stage will be used to assist business operations and accomplish their strategic objectives. The research conclusions indicated that the TOGAF method can be utilized as a tool to design the enterprise architecture of this information system and resulted in a general design architecture model in line with the vision and mission of the BLC and can be used to apply to other tutoring institutions that employ comparable business practices.